Building a Centre of Capital Accumulation: A Study of the Institutional Emergence of the French Private Equity Sector (from the Early 1980s to 2017). Issue 1 (2nd January 2021) - Benquet, Marlène; Bourgeron, Théo
ABSTRACT: This article describes a major shift in French capitalism: the emergence and development of the new private equity sector. It discusses the particularities involved in the construction of this capital accumulation centre in France, studying how an advantageous institutional arrangement was coproduced by fund managers, government and traditional industrial managers. As such, it takes an institutional approach focusing on the history of the rules that enable financial activities. This article's empirical material takes the form of (hitherto untapped) archives from the professional association of French private equity funds covering the period from 1984 to 2017, 12 interviews with former presidents of the association and ten interviews with partners of large French private equity funds.